Group exercise membership is associated with forms of social support, exercise identity, and amount of physical activity. Issue 2 (4th March 2022) - Golaszewski, Natalie M.; LaCroix, Andrea Z.; Hooker, Steven P.; Bartholomew, John B.
ABSTRACT: Exploring whether the mechanisms underlying the positive relationship between group exercise and physical activity are forms of social support – emotional, validation, informational, instrumental, and companionship and exercise identity. Participants ( n  = 506; M age = 34.3) completed a 235-item questionnaire assessing physical activity, exercise identity, social support, and other determinants of physical activity. Exploratory path analysis was used to model group exercise membership, forms of social support, exercise identity, and metabolic equivalent (MET) minutes/wk. Women and men had similar yet varying results. For women, group exercise membership was significantly associated with MET-minutes/wk ( β  = 0.11) and exercise identity ( β  = 0.17). There was a significant association between exercise identity and MET-minutes/wk ( β  = 0.38). Women perceived belonging to an exercise group provides emotional ( β  = 0.36), validation ( β  = 0.25), informational ( β  = 0.35), instrumental ( β  = 0.19), and companionship ( β  = 0.46) support. Validation ( β  = 0.11), informational ( β  = 0.21), and companionship ( B  = 0.17) were significantly associated with exercise identity for women. For men, group exercise membership was not significantly associated with MET-minutes/wk or exercise identity. Exercise identity was significantly associated with MET-minutes/wk ( β  = 0.46). Men perceived belonging to their group provides emotional ( β  = 0.31), validation ( β  = 0.32), informational ( β  = 0.33), and companionship ( β  = 0.34). Validation ( β  = 0.22), informational ( β  = 0.30), and emotional ( β  = 0.23) were significantly associated with exercise identity for men. Belonging to an exercise group is associated with forms of social support that strengthen exercise identity.